Interruptive time series analysis of GST upon non-performing non-housing property loans: case study from Malaysia / Tham Kuen-Wei, Rosli Said and Yasmin Mohd Adnan - Tham, Kuen-Wei,; Said, Rosli; Mohd Adnan, Yasmin (Accounting Research Institute (ARI), UiTM Shah Alam, 2021)
Value Added Taxes increases the cost of living and affect the ability of loan repayments indirectly. The introduction of the Goods and Services Tax (GST) in Malaysia in 2014 had garnered significant attention on its potential negative effects on the property industry. Coincidentally, there is a rise of non-performing non-housing property loans (NPNHLs) consisting of industrial and commercial property loans as GST was introduced and was in effect. The NPNHLs which consists of mainly industrial and commercial property loans faced a steep increase for the first time in 2014, after a long and consistent decline since 2007. From the inception stage of the GST to its effective implementation date, the Malaysian NPNHLs responded with a unique pattern that offers an opportunity for research. Hence, this study aimed to investigate and measure the intervention spill-over effects of GST upon the Malaysian NPNHLs. Utilizing a quasi-experimental design of interruptive time series regression analysis, it was found that there is a close and significant relationship between the implementation of GST and the rise of NPNHLs in Malaysia. The pre and post intervention of the GST regime was found to be in sync with the rise of non-performing non-housing property loans in Malaysia.